Semiological seizure classification of epileptic seizures in children admitted to video-EEG monitoring unit - Alan, Serdar; Yalnızoğlu, Dilek; Turanlı, Güzide; Karlı-Oğuz, Kader; Lay Ergün, Eser; Söylemezo?lu, Figen; Akalan, Nejat; Topçu, Meral (Turkish Journal of Pediatrics, 2015)
We aimed to determine seizure characteristics of pediatric patients with epilepsy, and evaluate if Semiological Seizure Classification (SSC) system is applicable in this cohort. We retrospectively studied 183 patients, aged between 3 months-18 years, admitted to the video-EEG monitoring unit (VEMU). Most patients suffered from intractable epilepsy with comorbidities, and had structural lesions. Seizures were classified based on ictal video-EEG recordings by using SSC system; 157 patients had only one seizure type, 26 had more than one seizure types. Overall 211 seizures and 373 semiologies were analyzed; 114 seizures (54%) had more than one semiological subtype. The most frequent semiology was motor seizures (78%), followed by dialeptic seizures (12%). The most common subtypes were simple motor seizures (49%); tonic seizures constituted (28.4%) of all semiologies. We conclude that SSC system is applicable for children with epilepsy admitted to VEMU; complementary EEG and imaging data are required for evaluation of patients with epilepsy.
WOS: 000378167800001
PubMed ID: 27186692
Keywords: Semiologic Seizure Classification; Epilepsy; Children; Video-EEG Monitoring